Structural Geomorphology and Tectonic Dynamism of the Lolodorf Segment, Nyong Complex, SW Cameroon - Eric José, Messi Ottou; Rémi, Etoundi Akoa Philémon; Benjamin, Ntieche; Martial, Ntomba Sylvestre; Saturnin, Evina Aboula Yannick; Paul-Désiré, Ndjigui (Indonesian Journal of Earth Sciences, 2025)
The study of the structural geomorphology and tectonic dynamism of the Lokoundjé and Nyong watersheds has made possible to discriminate the essential geological objects of the Lolodorf region (3°10’- 3°25’N, 10°40’- 10°55’E), in Southern Cameroon. This study has assessed the morphological and geological dynamism Lokoundjé and Nyong watersheds landscapes using both qualitative and quantitative data based on Digital Elevation Models (DEM) at 30 m resolution. Tectonic activities influence the topography of the land, which significantly affects the drainage system and geomorphological configuration of the area. Various tectonic indices were calculated to evaluate the evidence of tectonism. This include hypsometric curve (HC) and hypsometric integral (Hi), relative tectonic uplift (U), longitudinal Profiles (PL), knick-points (kp), stream-length gradient index (SL-index) swath profile, Asymmetrie factor (AF), transverse topographic symmetric factor (TTSF), Basin shape (Bs) and Relative tectonic activity (Iat) cumulatively with linear, area, relief morphometric parameters, and hydrographic on 2 delineated basins of the study area. These parameters were used to elucidate the dynamism of the structural geomorphology of the Nyong Complex to best constrain the morphostructural environment of this region. Imbricated circular structures, which could correspond to the Ngovayang fault, are highlighted in the Mvoule, Mboulé, and Mvilé sub-basins for the first time. New faults are mapped, and the most important are the ductile corridors of the Lokoundjé, Ngovayang, and Mvilé with NE-SW direction, and finally, the faults of Mée, Mélangué Boulou, Elon, and Nyamfende with NW-SE direction. The topographical variations allowed us to subdivide the area of Lolodorf and its surroundings into three levels or domains and to highlight three main morphological units, namely the low, medium, and high units. Tectonic structure lithology and differential erosion control the nature of the geomorphology and hydrographic network of the study area. The combined classification of Relative Tectonic Activity Index (Iat) and morphometric parameters of 2 basins categorised all the zones into two different classes: Class 2-High (2.00) and Class 3-Moderate (2.17 - 2.33). The basins with tectonic activities have a consistent relationship with structural disturbances and basin geometry. The active tectonic zonation of part of the two basins, according to geomorphological indices and morphometric parameters, suggests a significant influence of tectonic activity in some parts of the two basins. It highlights the tectonic activity that occurred over time and its influence on the overall morphology extending to the entire southwest margin of Cameroon.